1984
DOI: 10.1128/jb.157.2.637-642.1984
|View full text |Cite
|
Sign up to set email alerts
|

Cellular location of heat-labile enterotoxin in Escherichia coli

Abstract: We demonstrated that both the A and B subunits of heat-labile enterotoxin from Escherichia coli are located in the periplasm. The toxin was shown to form aggregates in Tris-EDTA buffers which are routinely used for isolating membranes. The aggregates pellet upon centrifugation, and this may explain why several previous investigators have concluded that enterotoxin is associated with membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1985
1985
1998
1998

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…Heat-labile enterotoxin (HLET) of E. coli, and the closely related cholera toxin (CT) of Vibrio cholerae, are synthesised as two subunits, each of which initially carries a typical NH2-terminal signal peptide [270,271,297,300,[342][343][344][345]. Both subunits are apparently required for their release from producing cells [346].…”
Section: Heat-labile Enterotoxin and Cholera Toxinmentioning
confidence: 99%
“…Heat-labile enterotoxin (HLET) of E. coli, and the closely related cholera toxin (CT) of Vibrio cholerae, are synthesised as two subunits, each of which initially carries a typical NH2-terminal signal peptide [270,271,297,300,[342][343][344][345]. Both subunits are apparently required for their release from producing cells [346].…”
Section: Heat-labile Enterotoxin and Cholera Toxinmentioning
confidence: 99%
“…Periplasmic fractions of E. coli were prepared by the method of Hirst et al (1984). Proteins were subsequently visualized by staining with Coomassie Brilliant Blue or electrobiotted onto nitrocellulose and probed with polyclonal rabbit anti-LTB antisera.…”
Section: Preparation and Analysis Of Periplasmic Extractsmentioning
confidence: 99%
“…Polypeptide 115 fractionated approximately equaify between ttie envelope and soluble fraction whilst poiypeptide 116 and authentic PBP5 fractionated mainly with the envelope fraction. To confirm that membrane association rather than formation of protein aggregates was responsible for the presence of the internally deleted PBP5 molecules in the envelope fraction, the membranes were floated up through sucrose gradients (Hirst et al, 1984), As shown in Fig. 5.…”
Section: Localization Of Internally Deleted Pbp5 Moleculesmentioning
confidence: 99%